CXCR2: From Bench to Bedside - Zarbock, Alex; Stadtmann, Anika (Frontiers in Immunology, 2012)
Leukocyte recruitment to sites of infection or tissue damage plays a crucial role for the innate immune response. Chemokine-dependent signaling in immune cells is a very important mechanism leading to integrin activation and leukocyte recruitment. CXC-chemokine receptor 2 (CXCR2) is a prominent chemokine receptor on neutrophils. During the last years, several studies were performed investigating the role of CXCR2 in different diseases. Until now, many CXCR2 inhibitors are tested in animal models and clinical trials and promising results were obtained. This review gives an overview of the structure of CXCR2 and the signaling pathways that are activated following CXCR2 stimulation. We discuss in detail the role of this chemokine receptor in different disease models including acute lung injury, COPD, sepsis, and ischemia-reperfusion-injury. Furthermore, this review summarizes the results of clinical trials which used CXCR2 inhibitors.